2019
DOI: 10.3390/en12173205
|View full text |Cite
|
Sign up to set email alerts
|

Study of Solid Calcium Diglyceroxide for Biodiesel Production from Waste Cooking Oil Using a High Speed Homogenizer

Abstract: Biodiesel has been one of the potential candidates in the field of renewable energy due to its biodegradability and non-toxicity in the natural environment. In addition, due to its high boiling point, the transportation of biodiesel is much safer than that of conventional fuel. However, the cost remains a challenge for the development of biodiesel. In this study, a homogenizer system, which can intensively minimize raw materials, is utilized as an effective approach to assist the production of both the calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The saponification value (SV) determination steps were: 2 g oil was put into a 250 mL cone bottle; next 0.5 N potassium hydroxide alcohol solution was added and mixed well in 1 h before some drops of 1% phenolphthalein indicator were added, and finally 0.5 N hydrochloric acid solution was added for titration. Then, the SV was determined using Equation (1) [29,30], and the AV was calculated via Equation (2) [33][34][35]. Where W is the oil weight (g), B designates blank titration amount (mL), S is sample titration amount (mL), V NaOH denotes the volume (mL) of the NaOH titrant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The saponification value (SV) determination steps were: 2 g oil was put into a 250 mL cone bottle; next 0.5 N potassium hydroxide alcohol solution was added and mixed well in 1 h before some drops of 1% phenolphthalein indicator were added, and finally 0.5 N hydrochloric acid solution was added for titration. Then, the SV was determined using Equation (1) [29,30], and the AV was calculated via Equation (2) [33][34][35]. Where W is the oil weight (g), B designates blank titration amount (mL), S is sample titration amount (mL), V NaOH denotes the volume (mL) of the NaOH titrant.…”
Section: Methodsmentioning
confidence: 99%
“…Homogenizers are often used in large-scale processing industries. It has been recently reported that homogenizers have the potential to be easily scaled up and significantly shorten the reaction time of transesterification [33][34][35]. However, there are relatively few studies related to homogenizer systems for biodiesel production, especially using a twostage synthesis method.…”
Section: Introductionmentioning
confidence: 99%
“…Glycerates of alkaline metals (sodium, potassium, lithium) are employed in the process of obtaining biodiesel fuel from vegetable oils and the waste of oil processing [4]. Calcium glycerate [5] is also used for this purpose. These compounds are catalysts for the transesterification process, as a result of which biodiesel fuel is produced, which is the esters of fatty acids.…”
Section: The Aim and Objectives Of The Studymentioning
confidence: 99%
“…Biodiesel is mainly derived from food oils [7,8], but the biodiesel produced is expensive due to the high cost of these feedstocks. To address this problem, waste and nonedible materials have been proposed as alternatives for producing biodiesel [9][10][11]. These oils can reduce biodiesel production cost, and they have no competition with the food supply [12,13].…”
Section: Introductionmentioning
confidence: 99%